2013
DOI: 10.1080/14459795.2012.754919
|View full text |Cite
|
Sign up to set email alerts
|

Markers of unsustainable gambling for early detection of at-risk online gamblers

Abstract: In this work we propose novel markers for identifying at-risk gamblers based on the concept of sustainability. The first hypothesis here verified is that problematic gamblers oscillate between intervals of increasing wager size followed by rapid drops, probably because they exceed their economic sustainability limits. Due to the non-periodic nature of these fluctuations, the proposed marker detects a certain occurring feature, such as a rapid drop in wager size, over a wide range of fluctuation periods, drop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 28 publications
1
49
1
Order By: Relevance
“…Overall, the results of these studies do not support earlier findings that Internet gambling is more addictive than land-based gambling [15,16,17,18,19,20,21,22,23,24,25,26]. Meanwhile, a growing body of research has focused on analyzing data sets of gambling accounts provided by various gambling operators [12,13,27,28]. …”
Section: Introductioncontrasting
confidence: 49%
“…Overall, the results of these studies do not support earlier findings that Internet gambling is more addictive than land-based gambling [15,16,17,18,19,20,21,22,23,24,25,26]. Meanwhile, a growing body of research has focused on analyzing data sets of gambling accounts provided by various gambling operators [12,13,27,28]. …”
Section: Introductioncontrasting
confidence: 49%
“…Over the past few years efforts have been made to design intelligent detection systems to identify markers of risky and disordered gambling using algorithms that analyse player behaviours and interactions (Dragicevic et al, 2011;Gainsbury, 2011;Auer and Griffiths, 2012;Braverman and Shaffer, 2012;Adami et al, 2013). These systems can be used to trigger warning signs for players or notify operators to check in with players in an attempt to minimise harms and prevent gamblers developing serious problems (Gainsbury, 2011;Haefeli et al, 2011).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…More information on the data set is available in Braverman and Shaffer (2012), Dragicevic 56 K.S. Philander Adami et al (2013). In order to provide a metric that is meaningful for actual implementation of these algorithms, the SLAs are compared based on their classification parameters: sensitivity, specificity, precision, accuracy, odds ratio and area under curve (AUC) (Sing, Sander, Beerenwinkel, & Lengauer, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Adami et al (2013) expand on Braverman and Shaffer (2012), and found two new markers for identifying at risk gamblers -the 'sawtooth' oscillation between increasing wager size and rapids drops, and number of games played (gambling involvement). Adami et al (2013) also note that the unsupervised k-means clustering process may be suboptimal.…”
Section: Empirical Studiesmentioning
confidence: 98%
See 1 more Smart Citation